2017
DOI: 10.2196/mhealth.8855
|View full text |Cite
|
Sign up to set email alerts
|

Usage Pattern Differences and Similarities of Mobile Electronic Medical Records Among Health Care Providers

Abstract: BackgroundRecently, many hospitals have introduced mobile electronic medical records (mEMRs). Although numerous studies have been published on the usability or usage patterns of mEMRs through user surveys, investigations based on the real data usage are lacking.ObjectiveAsan Medical Center, a tertiary hospital in Seoul, Korea, implemented an mEMR program in 2010. On the basis of the mEMR usage log data collected over a period of 4.5 years, we aimed to identify a usage pattern and trends in accordance with user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…For effective evaluations, benchmarks or thresholds are required for comparability to determine whether the results are desirable or not and what could be improved. [36] state that there are no scales or standard measures for assessing the findings' relevance or comparing similar interventions and their results. This literature review confirmed this statement as no policies, standards, or set benchmarks were used to conduct or compare the log analysis findings.…”
Section: ) Context Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For effective evaluations, benchmarks or thresholds are required for comparability to determine whether the results are desirable or not and what could be improved. [36] state that there are no scales or standard measures for assessing the findings' relevance or comparing similar interventions and their results. This literature review confirmed this statement as no policies, standards, or set benchmarks were used to conduct or compare the log analysis findings.…”
Section: ) Context Of Analysismentioning
confidence: 99%
“…9. User groups were identified according to the time-based [26,267,36], location-based [27,37], or device-based [27,[36][37][38]] frequency of usage. The time-based usage can be grouped into three main user groups according to the frequency of use: Active users (high-usage frequency), occasional users (medium or low usage frequency) and inactive users (nonusage), as summarized by Table 5.…”
Section: ) Concepts and Indicatorsmentioning
confidence: 99%
“…Viewing electronic health records (EHRs) on mobile devices such as tablets and smartphones has increased lately and is becoming more common in the health care sector in many developed countries. Nurses form the largest group in health care that uses EHRs and their mobile versions [ 1 ]. A previous study reported that use of mobile versions of EHR is common in hospitals, especially during the handover period and ward hours [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses form the largest group in health care that uses EHRs and their mobile versions [ 1 ]. A previous study reported that use of mobile versions of EHR is common in hospitals, especially during the handover period and ward hours [ 1 ]. Nurses have been found to use the mobile version of EHR mainly for viewing inpatient lists, nursing notes, alerts, and patients’ clinical data with high frequency [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been made to analyze log data from mEHRs for the evaluation of providers’ workflow [14,15]. Even among doctors, the usage paths are likely to differ according to their specialties, resulting in different work processes [13].…”
Section: Introductionmentioning
confidence: 99%